Neural Transplants From Human Induced Pluripotent Stem Cells Rescue the Pathology and Behavioral Defects in a Rodent Model of Huntington’s Disease - Yoon, Yongwoo; Kim, Hyun Sook; Hong, Chang Pyo; Li, Endan; Jeon, Iksoo; Park, Hyun Jung; Lee, Nayeon; Pei, Zhong; Song, Jihwan (Frontiers in Neuroscience, 2020)
Huntington’s disease (HD) is a devastating, autosomal-dominant inheritance disorder with the progressive loss of medium spiny neurons (MSN) and cortico-striatal connections in the brain. Cell replacement therapy has been proposed as a potential therapeutic strategy to treat HD. Among various types of stem cells, human induced pluripotent stem cells (iPSCs) have received a special attention to develop disease modeling and cell therapy for HD. In this study, we investigated the therapeutic effects of neural precursor cells derived from a human induced pluripotent stem cell line (1231A3-NPCs) in the quinolinic acid (QA)-lesioned rat model of HD. 1231A3-NPCs were transplanted into the ipsilateral striatum one week after QA lesioning and the transplanted animals showed significant behavioral improvements, judged by the staircase, rotarod, stepping, apomorphine-induced rotation and cylinder tests for up to 12 weeks. Transplanted 1231A3-NPCs also partially replaced the lost neurons, enhanced endogenous neurogenesis, reduced inflammatory responses, and reconstituted the damaged neuronal connections. Taken together, these results strongly suggest that neural precursor cells derived from induced pluripotent stem cells can be potentially useful to treat HD in the future.